2001
DOI: 10.1177/153537020122601010
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Agonist Evoked Vasoconstrictor Responses in the Perfused Mesenteric Vascular Bed of Streptozotocin Diabetic Rats

Abstract: We compared agonlst-evoked responses In the perfused mesenteric vascular bed (MVB) of streptozotocln (STZ) diabetic Sprague-Dawley rats 2 and 14 weeks after Induction of diabetes. Endothelln-1 (ET-1h methoxamine (MTXh and KCI-evoked vasoconstrictor responses were unchanged In 2-week-old diabetic rats. In contrast, both the sensitivity (P < 0.01) and the maximal vasoconstrictor responses (P < 0.05) to ET-1 were attenuated In 14-week-old diabetic rats, whereas endothelln plasma levels were Increased (P < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In addition to impaired acetylcholine-evoked responses in diabetic models, attenuated pressor responses to vasoconstrictor agonists, such as methoxamine and endothelin (ET)-1, have been reported [9,10]. Indeed, we have observed attenuated responses to ET-1 and methoxamine both in vivo and in vitro in the isolated perfused mesenteric vascular bed [11]. Thus, for comparison with vasodilator responses evoked by acetylcholine, we also recorded vasoconstrictor responses to ET-1 and methoxamine.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to impaired acetylcholine-evoked responses in diabetic models, attenuated pressor responses to vasoconstrictor agonists, such as methoxamine and endothelin (ET)-1, have been reported [9,10]. Indeed, we have observed attenuated responses to ET-1 and methoxamine both in vivo and in vitro in the isolated perfused mesenteric vascular bed [11]. Thus, for comparison with vasodilator responses evoked by acetylcholine, we also recorded vasoconstrictor responses to ET-1 and methoxamine.…”
Section: Introductionmentioning
confidence: 85%
“…Both attenuated and exaggerated responses to α-1 agonists have been reported [11,32]. The ability of VEGF to activate protein kinase C, through both flt-1 and flk-1 receptors, has been reported [33].…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the effects, it is often thought that autonomic neuropathy underlays these (4,8,16,27). A common finding is that vessels from diabetic rats (7, 28 -30) and rabbits (8,26) have increased sensitivity to adrenergic agonists, although this observation is not universal (16,19,22,25). Similarly, effects of diabetes on sympathetically evoked responses have varied from vasoconstriction being increased (26,29,30), remaining the same (8,21,25), or decreasing (16).…”
mentioning
confidence: 93%
“…Many studies have shown that an altered vascular responsiveness characterized by increased reactivity to vasoconstrictors and impaired vasodilation exists in the diabetic state (13)(14)(15)(16)(17). We have demonstrated that chronic hyperinsulinemia in fructose-drinking rats, an experimental model for insulin resistance and type 2 diabetes, facilitates adrenergic nerve-mediated vasoconstriction, which is associated with attenuated CGRPergic nerve-mediated vasodilation (18).…”
Section: Introductionmentioning
confidence: 87%